Calcium silicate hydrate–embedded porous concrete for efficient phosphate removal and recovery in concentrated eluates - Worawit Wongniramaikul; Aree Choodum; Pakorn Pasitsuparoad; Suparat Cotchim; Chanadda Phawachalotorn; Tarawee Taweekarn (Water Research X, 2025)
• Porous concrete–CSH column achieves >99% continuous–flow phosphate removal. • Surface microprecipitation driven by Ca²⁺/OH⁻ from added (40%) and in situ CSH (60%). • Nonlinear Yoon–Nelson model best fits breakthrough data in synthetic and real water. • PC–CSH column removes 99.3% of phosphate from municipal wastewater with minimal effect. • PC–CSH column enables ∼100% phosphate recovery and reuse for up to 4 cycles. Phosphate remediation and recovery from wastewater remain challenging due to limitations in adsorbent stability and real–world applicability. This study presents a sustainable porous concrete–calcium silicate hydrate (PC–CSH) column engineered for continuous–flow phosphate removal and resource recovery. Synthesized CSH nanoparticles were incorporated into a porous cement matrix, and comprehensive characterization confirmed the formation of calcium phosphate phases, including hydroxyapatite (HAP), CaHPO₄, and Ca(H₂PO₄)₂. The results indicate that surface-induced microprecipitation, driven by Ca²⁺ and OH⁻ released from both added and in situ–formed CSH, is the dominant removal mechanism. Externally added nanoparticles contributed 40.05% of total uptake, while the remainder originated from CSH generated during cement hydration. Breakthrough analysis showed that increasing column height enhanced longevity, whereas higher influent phosphate concentration and flow rate accelerated saturation. Under optimal conditions (7.5 cm column, 50 mg L⁻¹ phosphate, 10 mL min⁻¹ flow), the system achieved >99% removal with a total adsorption capacity of 3599.7 mg. The nonlinear Yoon–Nelson model best described the breakthrough behavior. Application to real municipal wastewater (initial phosphate 4.57 mg L⁻¹) achieved 99.3% removal with minimal influence from coexisting anions (SO₄²⁻, NO₃⁻, CO₃²⁻). Phosphate was efficiently recovered using 0.5 M HCl (100.4% desorption), and performance was restored by reloading fresh PC–CSH slurry. The column retained 73.9% phosphate removal efficiency after four adsorption–desorption cycles with real wastewater, demonstrating excellent reusability and practical potential. Overall, the PC–CSH column offers a robust, semi–regenerable platform for sustainable phosphate mitigation and recovery in wastewater treatment.
Keywords: Phosphorus and nutrient management; Layered Double Hydroxides Synthesis and Applications; Soil and Water Nutrient Dynamics